Elements of applied statistics - Oyeka, Cyprian A. (Enugu, Nigeria : Modern Printers, 2002)
An introductory textbook of statistical methods in simple ways to grasp, more concrete and relevant to contemporary issues.
Includes index.
oif 16/04/15
Loans
Keywords: Statistics